Potensi Ekstrak Air Dan Ekstrak Etanol Daun Avicennia Marina Sebagai Nutraceutical - Mardiyanto Riski Hartono (LPPM Universitas PGRI Adi Buana Surabaya, 2021)
This research was conducted to prove that the leaves of avicennia marina contain ingredients that are potential as nutraceuticals, as well as to determine the comparison of the extraction results using water extract and ethanol extract. Avicennia marina leaves collected randomly and turn it into powder. The avicennia marina leaves powder processed with water extraction and ethanol extraction. The result of extraction process were tested by phytochemical screening tests to determine the content of flavonoids, alkaloids, tannins, steroids, triterpenoids, saponins, and examined for flavonoid levels by thin layer chromatography (TLC). The results of phytochemical screening test for ethanol extract of avicennia marina leaves showed positive results for the content of flavonoids, alkaloids, tannins, steroids, and saponins, but showed negative results for triterpenoid content. The water extract of avicennia marina leaves showed positive results for the content of flavonoids, alkaloids, tannins, and steroids, but showed negative results for saponins and triterpenoids content. At thin layer chromatography test, the flavonoid content showed that ethanol extract of avicennia marina leaves had 2.46%, while water extract of avicennia marina leaves had .80% of flavonoid content percentage. The results of ethanol extraction and water extraction from the leaves of avicennia marina show that they contain phytochemicals which are beneficial for health, and have the potential as a nutraceutical for medicinal purposes.